The effects of extracurricular physical education classes on gross motor development in primary school children - pilot study - Skowroński Waldemar; Skowrońska Marianna; Rutkowska Izabela; Bednarczuk Grzegorz; Kaźmierska-Kowalewska Kalina Maria; Marszałek Jolanta (Sciendo, 2019)
Study aim: The aim of the study was to investigate the changes in gross motor skills in children participating and not participating in a project of extracurricular physical education classes in primary schools called "From fun to sport".